Terapi Latihan Dan Ultrasound Dalam Meningkatkan Kemampuan Fungsional Pada Total Hip Replacement - Utami, Retno; Djawas, Faizah Abdullah (Jurnal Fisioterapi Terapan Indonesia, 2023)
Total Hip Replacement (THR) is an orthopedic surgical procedure to replace the cartilage of the acetabulum and collum femur with a prosthesis, which is an artificial ball and rod made of metal. This causes various problems including limited joint range of motion (LGS), decreased muscle strength, decreased balance, and decreased functional ability. The application of modalities in the form of ultrasound is believed to be able to reduce pain and the application of exercise therapy in the form of Stretching Exercise, ROM Exercise, Strengthening Exercise, Balance Exercise, and Gait Training is believed to be able to improve functional abilities by reducing spasm, increasing LGS, increasing muscle strength, increasing balance, and improving walking patterns. The purpose of this study is to determine the effectiveness of exercise therapy and ultrasound in improving functional ability in total hip replacement. Methods: Single case study in a 64-year-old woman. Therapeutic modalities in the form of ultrasound and exercise therapy in the form of Stretching Exercise, ROM Exercise, Strengthening Exercise, Balance Exercise, and Gait Training with six evaluations. Assessment of pain intensity using VAS, LGS assessment using a goniometer, muscle strength assessment with MMT, and functional ability assessment using HHS parameters. Results: There is a decrease in pain, an increase in the scope of joint motion and muscle strength and an increase in functional ability. Conclusion: This study shows that modality therapy interventions in the form of ultrasound and exercise therapy in the form of Stretching Exercise, ROM Exercise, Strengthening Exercise, Balance Exercise, and Gait Training can improve functional abilities in cases of total hip replacement as measured using HHS parameters.